Ernst-Wolfgang Böckenförde's Approach to Natural Law as Normative Legal Ethics. (15th January 2018) - Hahn, Judith
ABSTRACT: This article examines the concept of natural law in the writings of Ernst-Wolfgang Böckenförde, a legal scholar who has influenced the German debates on legal theory for more than half a century. Böckenförde interprets natural law as normative legal ethics. He defends the importance of law being legitimized, directed, and corrected by ethics. But what kind of legal ethics may render this service to modern secular law? Böckenförde criticizes Catholic natural law doctrine which, in over-emphasizing a natural law of principles, is largely unable to respond to concrete ethical questions which are posed with regard to the law today. Nevertheless, he still promotes religious thought as helpful for the foundation of secular law. Here, Böckenförde supports a political theology that encourages Christians to engage in public discourses on law and politics. This idea is discussed from the point of legal theory and Catholic Theology.